PENGARUH PEMASARAN ONLINE TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION DIKALANGAN MAHASISWA: (STUDY KASUS MAHASISWA FISIPOL UNIVERSITAS ISLAM RIAU) - Amelia Rahmi; Moris Adidi Yogia (UIR Press, 2015)
Fashion is a primary need of every human being. object of this study is that consumerswho buy fashion products online. The four online stores such as Jenawi T-shirts, RiauFashion, Pekanbaru store, and Aisyah Muslim Station is one of the online stores thatexist in Pekanbaru. As for the sale is fashion products such as clothes, bags, shoes, andother fashion accessories. In marketing online store using online marketing. Onlinemarketing can increase sales and build long term relationships with consumers. Onlinemarketing is what is considered by the online store is the most effective marketing. Thisstudy took a sample of 200 respondents using purposive (Dependence) and in analyzingthe data using descriptive and quantitative methods.Types and sources of data used areprimary data and secondary data. method of data collection is done by distributingquestionnaires to the respondents buyers of fashion products online and interviews tothe online store owner to obtain the results of this research conclusion that onlinemarketing in terms of convenience, the information, which is a little seduction, problemrecognition, information search, evaluation of alternatives, and the purchase decisionobtain a score of 11714 with score interval 11668-15000 criteria and classified into(Very Influental) this shows that the influence of online marketing on purchasingdecisions. from the research can be seen that online marketing has a positive The effectof online marketing on purchasing decisions among students of fashion products FisipolIslamic Univesity of Riau